SOSIALISASI CARA MENYARING INFORMASI HOAKS DI TENGAH PANDEMI COVID-19 - Fajria Noviana; Zaki Ainul Fadli; Bernadetta Venezia (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2021)
Since the covid-19 pandemic emerged in early 2020, people have been required to be more careful in their activities. Various guidelines for health procedures can be easily found in public places. However, until mid-2021, people were not only faced with the threat of the covid-19 virus, but also with the rampant hoax news and disinformation surrounding this pandemic. Therefore, this community service activity was held with the aim to give an understanding of what is meant by hoax, disinformation and infodemic, as well as to convey how to filter hoax about the covid-19 pandemic. The method used in this online community service activity is in the form of lectures, discussions, and questions and answers regarding information circulating in the mass media about covid-19 pandemic, including those circulating in WhatsApp group conversations. There are four ways to filter hoax information circulating in mass media and social media, namely by: 1) paying attention to the title and content; 2) check the source; 3) stop its spread; and 4) report it to the authorities. Through this online activity, we hope that people would be wiser in using the internet and social media to find and disseminate information related to covid-19 pandemic.Keywords : hoax; disinformation; infodemic; pandemic; covid-19